The Tourism potential in Al Haffeh and its development prospects - سعيد, ابراهيم; حسو , عمار محمد (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The research deals with the elements of tourism activity in the Al Haffeh region by evaluating the current reality of natural and human resources and their importance in tourism. Then the historical and archaeological sources and their importance in tourist attractions and from here came the importance of research in dealing with the reality of tourism activity in the Al Haffeh region and one of most important results shown by the study in the concentration of tourism activity in the Slanfah area of the Al Haffeh region which is characterized by the uniqueness of it's resources and it's distinction at the level of Lattakia governorate to the desired results, and then shed light on the problems that reflect negatively on the tourism sector in the possibilities for it's development in the investment of tourism resources and the development of these resources and the identification of more general naturally distinct sites in the region and commission for tourism investment and thus making the region a pole of world tourism, which leads to making tourism a mainstay one of the pillars of the national economy.